Development of problem-based learning materials on linear programming to facilitate students' mathematical problem-solving skills - Situmorang, Ruth Sahana; Hutapea, Nahor Murani; Armis (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to develop Problem-Based Learning (PBL) instructional tools, including a syllabus, lesson plans, and student activity sheets, to enhance students' mathematical problem-solving skills. The development process follows the 4-D model, consisting of four stages: Define, Design, Develop, and Disseminate. Data were collected through interviews, observations, and questionnaires, using validation sheets and student response surveys as instruments. The validity of the instructional tools was assessed by experts, with results indicating high validity, with average scores of 3.82 for the syllabus, 3.93 for the lesson plans, and 3.79 for the student activity sheets. Additionally, the practicality of the LAS was tested in both small and large groups, showing high practicality with average scores of 3.52 and 3.64, respectively. These findings indicate that the developed instructional tools meet the required standards of validity and practicality, making them suitable for classroom use. This study successfully created PBL-based instructional tools that effectively support the development of students' mathematical problem-solving skills and are expected to positively impact mathematics learning.